2015
DOI: 10.1177/0899764015595721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Determinants of Revenue Sources for International NGOs

Abstract: Securing financial sustainability through fundraising and other forms of financing is a critical issue for many nonprofit organizations. This article extends the benefits theory by adding beneficiary and organizational characteristics to it and examines how these characteristics affect revenue source composition. Based on a survey of International Nongovernmental Organizations (INGOs) with headquarters in Switzerland, the results quantitatively demonstrate a predictive relationship between programmatic and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Benefits theory proposes that a nonprofit’s revenue streams should reflect whether the organization’s program activities primarily generate private benefits to individuals, group benefits to identifiable subgroups of society, public benefits to society at large, or trade benefits to organizations or individuals that supply resources to nonprofits (Young, 2006). Subsequent research has largely confirmed the test implications of benefits theory, finding that nonprofits whose programs provide public benefits tend to have more donative funding, while nonprofits whose programs provide private benefits tend to have more earned income (Aschari-Lincol & Jäger, 2015; Fischer, Wilsker, & Young, 2011). The match between program benefit and revenue source may be taken as an indication of the appropriateness of an organization’s income portfolio.…”
Section: Domains Of Managerialismmentioning
confidence: 95%
“…Benefits theory proposes that a nonprofit’s revenue streams should reflect whether the organization’s program activities primarily generate private benefits to individuals, group benefits to identifiable subgroups of society, public benefits to society at large, or trade benefits to organizations or individuals that supply resources to nonprofits (Young, 2006). Subsequent research has largely confirmed the test implications of benefits theory, finding that nonprofits whose programs provide public benefits tend to have more donative funding, while nonprofits whose programs provide private benefits tend to have more earned income (Aschari-Lincol & Jäger, 2015; Fischer, Wilsker, & Young, 2011). The match between program benefit and revenue source may be taken as an indication of the appropriateness of an organization’s income portfolio.…”
Section: Domains Of Managerialismmentioning
confidence: 95%
“…Compared to RDT, benefits theory takes a more direct view of resources for social purpose organizations by connecting the benefits of the provided services/goods to the types of revenue sources (Aschari-Lincoln and Jäger 2016). Benefits theory proposes that social purpose organizations achieve their social missions and generate benefits for various beneficiary groups through the provision of goods and services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical research in public administration has provided substantial support for benefits theory (Aschari-Lincoln and Jäger 2016; Fischer, Wilsker, and Young 2011). Fischer, Wilsker, and Young (2011) is the first study to empirically test the theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an organisational context, financial sustainability refers to long-term business survival (Costanza & Patten, 1995), the ability of an organisation to generate necessary revenues to cover expenses (Aschari-Lincoln & Jäger, 2016;Manuel Pedro Rodríguez et al, 2018), and be able to pay debts in the long term (Nyankomo & Aziakpono, 2015). In the context of micro-enterprises, similar to small business literature, their long-term survival (or financial sustainability) is reflected through profitable, self-funding operations, independent of ongoing government or non-government (e.g., NGO) assistance (Lohmer, 2008;Sheremenko et al, 2017;Strier, 2010).…”
Section: A Review Of Financial Sustainability and Success In Poverty Alleviationmentioning
confidence: 99%